Moleculargenetic analysis of acdS gene of Pseudomonas putida B-37 - Melnikava, Alesia A.; Leanovich, Sviatlana I.; Khramtsova, Alena A. (Experimental Biology and Biotechnology, 2017)
In current work PCR-screening of bacterial collection of genus Pseudomonas was made with the purpose to check the presence of acdS gene which is coding enzyme ACC deaminase. ACC deaminase can inhibit synthesis of stress ethylene that is harmful for the growth and development of plants. This gene was observed among three of five bacterial strains (P. putida B-37, P. putida B-28, P. putida KT 2442). Nucleotide sequence of the fragment corresponding to acdS gene of P. putida B-37 was taken and analyzed in silico. As a result, it was proven that there is acdS gene and it codes the protein ACC deaminase. Using of ACC deaminase will lead to increasing of stress ethylene level and negative influence on the plants of different environmental factors.